2022
DOI: 10.21203/rs.3.rs-2357522/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PCP-ACO: a deadline-constrained workflow scheduling algorithm for cloud environment

Abstract: A cloud computing environment is the most popular choice for workflow execution, as it gives customers on-demand access to computing resources. However, in cloud workflow scheduling, cloud-native requirements regarding QoS requirements such as monetary cost and execution time should be taken into account. This paper proposes PCP-ACO, a list scheduling algorithm for minimizing the execution cost of a workflow, while meeting its user-defined deadline in cloud environments. In PCP-ACO, first a topological sort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Finally, results revealed that WDQN-RL outperforms above algorithms in view of makespan, cost. Energy consumption, makespan, Migration time are measured in [43] by formulating a task scheduling algorithm by using a hybrid approach. This hybrid approach uses capuchin search as local search process and inverted ACO as global search process.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, results revealed that WDQN-RL outperforms above algorithms in view of makespan, cost. Energy consumption, makespan, Migration time are measured in [43] by formulating a task scheduling algorithm by using a hybrid approach. This hybrid approach uses capuchin search as local search process and inverted ACO as global search process.…”
Section: Related Workmentioning
confidence: 99%
“…[40] NSGA Energy consumption and makespan [41] GA-BF energy consumption, response time, makespan [42] Improved ACO resource utilization, cost, deadline violation rate, makespan. [43] MCC algorithm makespan and average cloud utilization [44] RL-EERA accuracy, CPU Utilization, Response time. [45] QEEC task response time, energy consumption and CPU utilization [46] DQN Based Multi agent RL Task completion time and cost.…”
Section: Related Workmentioning
confidence: 99%